(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2023)
A person’s perceived body image is how he evaluates his physical appearance. Because of their desire to conform to existing beauty standards, young women are the most vulnerable group to body shape dissatisfaction. The aim of this study was to analyze body image perception and food consumption quality of normal- and over-nourished female adolescents in Bandung City. Cross-sectional study was conducted and 145 normal nutrition status of female adolescents and 54 over nutrition female adolescents aged between 15-17 years old were selected as the subjects. This study was conducted in 18 randomly selected senior high schools in Bandung City. Body image perception data was collected using Multidimensional Body-Self Relations Questionnaire-Appearance Scales (MBRSQ-AS) instrument, meanwhile food consumption quality data was collected using Healthy Eating Index (HEI) instrument. Most of subjects had normal body image perception with no subject had good food consumption quality. The result showed significant difference in several subscales of body image perception, namely appearance evaluation, body areas satisfaction, overweight preoccupation, and self-classified weight in female adolescents with normal and over-nutrition (p<0.05). However, there was no significant difference in subject’s food consumption quality (p>0.05).